ETNOMATEMATIKA: EKSPLORASI KESENIAN MUSIK CALUNG BANYUMASAN SEBAGAI SUMBER PEMBELAJARAN MATEMATIKA - Kusno Kusno; Gunawan Gunawan; Makhful Makhful (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The selection of material that is contextual and based on student culture is essential for improving the quality of learning mathematics. This study aims to examine, explore, and explore Calung Banyumasan music as a source of learning mathematics that is contextual and easy to understand. This research is qualitative with an ethnographic approach because it examines a particular cultural system (Banyumasan art) from an ethnomathematics perspective. The subjects in this study were three humanists, practitioners, and mathematicians related to Calung Banyumasan musical arts, and the research object was Calung Banyumasan instruments. Data collection methods use in-depth interviews, observation, documentation, and field notes. The data analysis method was carried out descriptively based on the results of the meaning and translation of the phenomena found based on the results of the informant's conception, the results of observations combined with the researcher's language after an in-depth understanding was carried out. Triangulation and Forum Group, Discussion was used to test the data's validity and the effects of data analysis. The research results show that Calung Banyumasan music art has mathematical wealth, especially in Geometry (parallelism, congruence, plane shapes, and curved side shapes) and Algebra (compound functions, arithmetic sequences, series, and inverse comparisons of values). Besides that, Calung Banyumasan music also has a lot of valuable philosophical content for human life.